Study of the fungus Botrytis cinerea that damages strawberry species - Ismagulova, A.B.; Tulegenova, Zh.A.; Spanbayev, A.D.; Shalabaeva, A.M. (Fundamental and Experimental Biology, 2023)
The paper studies the causative agent of fungal gray rot, a harmful pathogen that affects the fruits of strawbe r-ry species that are in high demand and berries of which have beneficial properties. The purpose of the re-search work: to isolate the fungus Botrytis cinerea, the causative agent of the harmful pathogen of the fruit Fragaria moschata, and to study it comprehensively. That is, to identify the pathogen by separating fungal cultures and identifying it by molecular-genetic method and determining its pathogenicity by re-inoculation. The disease of gray rot causes enormous damage to the strawberry plant not only during the growing season, but also after harvesting, worsening the quality of the product. Therefore, a comprehensive study and identification of harmful fungal pathogens will serve as a practical basis for preventing the disease and organizingmeasures to combat it. Isolation of accumulative and pure cultures by growing in a solid nutrient medium from damaged strawberry fruits and identification by morphological-cultural and molecular-genetic methods, as a result of the analysis, 99.62 % corresponded to the species Botrytis cinerea. Pathogenicity is proven by inoculation in strawberry fruits. The pathogen fungus Botrytis cinerea, which causes significant damage to Strawberry Fields in the country, has been identified by modern molecular and gentian methods and serves as the basis for organizing further measures to combat it.